Synthesis and Degradation of Hexamethylene Triperoxide Diamine (HMTD). Issue 2 (2nd December 2015) - Oxley, Jimmie C.; Smith, James L.; Porter, Matthew; McLennan, Lindsay; Colizza, Kevin; Zeiri, Yehuda; Kosloff, Ronnie; Dubnikova, Faina
Abstract: The synthesis and decomposition of hexamethylene triperoxide diamine (HMTD) were studied. Mechanisms were proposed based on isotopic labeling and mass spectral interpretation of both condensed phase products and head‐space products. Formation of HMTD from hexamine appeared to proceed from dissociated hexamine as evident from scrambling of the 15 N label when synthesis was carried out with equal molar labeled/unlabeled hexamine. Decomposition of HMTD was considered with additives and in the presence and absence of moisture. In addition to mass spectral interpretation, density functional theory (DFT) was used to calculate energy differences of transition states and the entropies of intermediates along different possible decomposition pathways. HMTD is destabilized by water and citric acid making purification following initial synthesis essential in order to avoid unanticipated violent reaction. Abstract :